RANCANG BANGUN WEBSITE SENTRA UKM MERR - Kadarisman, Hendry Haryo; Wurijanto, Tutut; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Sentra UKM MERR is a showroom dedicated for UKM on Surabaya. It main purpose is to help promote the products of UKM on Surabaya. DISPERDAGIN Surabaya as the one who supervise the business on Sentra UKM MERR use two methods to promote Sentra UKM MERR. These two methods resulting in inability to monitor the result of promotional act. and Sentra UKM MERR did not have promotional target, and did not have a further means to use the data registered at the guestbook provided on Sentra UKM MERR. Based on these problems, a website that is able to do the promotional function and able to provide data of the users is developed. This website will provide users with information regarding product and UKM that produce it. Website also provide an article to support in influencing search engine for popularity. This kind of system will produce three items for Sentra UKM MERR which is sales report, private data of registered users, and activity data of users.